Leukoencephalopathy and cerebral edema as the presenting manifestations of SLE in an ANA-negative adolescent female: a case report and review of literature - Alexandra Theisen; Paroma Bose; Christina Knight; Melissa Oliver (BMC, 2020)
Abstract Background Systemic lupus erythematosus (SLE) is an autoimmune disease with various clinical manifestations involving multiple organ systems. Neuropsychiatric manifestations of SLE have been associated with increased morbidity and mortality, thus it is important to recognize and diagnose the disease entity and treat early. When neuropsychiatric symptoms are involved, typically there are many other systemic features to aid in the diagnosis of SLE. Many autoantibodies have been discovered and are used to help diagnose SLE. The antibody present in most cases of pediatric SLE, as well as in many other rheumatic diseases, is the nonspecific antinuclear antibody (ANA). The ANA is a commonly used screening tool by primary care physicians when evaluating a patient with a possible rheumatic disorder. However, a small subset of SLE patients, 1-5%, present with a negative ANA, and it is important to keep SLE on the differential diagnosis in specific instances when a thorough infectious, metabolic and neurological workup has been completed and proven to be inconclusive. Case presentation This case involves a Hispanic adolescent female with a negative ANA who presented with diffuse cerebral edema secondary to leukoencephalopathy due to SLE with central nervous system involvement. She was normotensive on presentation and relatively symptom free aside from headache. She had an extensive workup while inpatient involving metabolic, infectious disease, rheumatology, and neurology prior to obtaining the diagnosis of SLE. She was treated with cyclophosphamide and rituximab with appropriate disease response. Conclusions A review of the literature revealed 12 cases with SLE presenting with or developing diffuse cerebral edema and/or leukoencephalopathy. Our patient's case differs in that she was also ANA negative despite other autoantibody positivity. While she did have low complements and transient leukopenia, she did not present with other signs of organ involvement, which made the diagnosis of SLE with neuropsychiatric involvement quite challenging. We discuss the importance of keeping SLE on the differential diagnosis despite a negative ANA in complex cases after thorough workup has been unrevealing, and to consider initial screening with not only the ANA but also dsDNA and complements to avoid missed diagnoses.